KONSEP INTEGRATED LIVABLE EDUCATIONAL AREA DI KAWASAN PENDIDIKAN TINGGI, TEMBALANG KOTA SEMARANG - Novia Sari Ristianti (Jurnal Riptek, 2019)
Liveable cities are related to Quality of life as measured by indicators of livability, accessibility of infrastructure such as transportation, clean water, sanitation, adequate housing, clean air, green spaces and a comfortable environment to live in. One of the areas studied in terms of livability is the Tembalang UNDIP education area. The removal of the Undip education area, which was originally located in Pleburan, has both positive and negative impacts on the social, economic and environmental aspects of the Tembalang village. The problem of this area is the existence of non-integrated settlements, transportation problems where students are reluctant to use public transportation, the availability of open space as public spaces and flooding during the rainy season due to poor drainage. Therefore, the aims is to formulate a concept of the concept of livable educational areas in the area around Tembalang UNDIP. The method used is quantitative with the SWOT method. As for the results of research on the concept of integrated educational area, there are four aspects. In livable settlement aspect, it is necessary to provide vertical housing for students. In livable transportation aspect, the need for public transportation that is integrated and easy to use. The livable open space aspect, the provision of public open spaces which facilitate student activities. The livable drainage infrastructure by providing eco-drainage. The conclusion is that Tembalang as a tertiary education area can become a livable area with the concept of integrated educational area.